Medical Oxygen Safe Handling During Coronavirus Pandemic: Short Review - H. Al-Dahhan, Wedad; Kadhom, Mohammed; S. Abdallh, Mustafa; A. Yousif, Emad; A. Mohammed, Salam (Al-Nahrain Journal of Science, 2022)
Background: When oxygen is mentioned, we think of air that we inhale. However, oxygen that is used for medical purposes and treatments should be highly pure (> 99.5 %). Materials and Methods: Medical oxygen can be used for oxygen therapy, anesthetics, resuscitation, and life support. Using excess oxygen could cause several side effects, including nasal irritation, hypoxic respiratory drive, and pulmonary oxygen toxicity.  Results: During the COVID-19 pandemic, while there is an increasing demand for medical oxygen, it can be concluded that a number of health care centers are not equipped to handle oxygen cylinders in a safe way. Also, the household use of oxygen cylinders can be considered as a new risk in terms of the lack of safe use of compressed gases. Conclusion: Several precautions and some case studies are reported in this paper, mainly are the basic recommendations for safe medical oxygen gas handling.